2018
DOI: 10.3329/bjsir.v53i2.36677
|View full text |Cite
|
Sign up to set email alerts
|

Parameters associated with growth factors of five fish species in the Atrai River, Dinajpur, Bangladesh

Abstract: For evaluation of Fulton's condition factor (CF f ), relative body weight (BW r ) and form (a 3.0 ) factor affecting growth, 5 fishes (Aspidoparia jaya, Gagata cenia, G. youssoufi, Salmophasia bacaila and S. phulo) were collected from the Atari River in Dinajpur district of Bangladesh. Significant differences (p < 0.05) were recorded among the values of CF f (0.47-1.56) but not for BW r (79.60-128.39). Based on CF f values, analysis of similarities (ANOSIM, p < 0.01) revealed that maximum distances (R = 0.9946… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 15 publications
5
12
0
Order By: Relevance
“…According to Froese [ 57 ]; prohibiting catching first mature fish and letting them grow up to optimum length of 6.0 cm and greater than 5.5 cm size fish as well as 6.0–6.5 cm size group of G. cenia are suggested for exploitation. Comparing this value with the calculated L m of other water bodies, it’s found that the values are almost similar to the calculated value of the Atrai River, Dinajpur, Bangladesh [ 32 , 36 ] and Payra River, Bangladesh [ 33 ], but is much lower than the calculated value of the Ravi River, North-western India ( Table 5 ), which may be attributed to the geographical variation. Tactlessly, this research conveys the first effort to estimate the size at sexual maturity and optimum catchable length for this fish, hence comparisons with other findings will be required in the future.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…According to Froese [ 57 ]; prohibiting catching first mature fish and letting them grow up to optimum length of 6.0 cm and greater than 5.5 cm size fish as well as 6.0–6.5 cm size group of G. cenia are suggested for exploitation. Comparing this value with the calculated L m of other water bodies, it’s found that the values are almost similar to the calculated value of the Atrai River, Dinajpur, Bangladesh [ 32 , 36 ] and Payra River, Bangladesh [ 33 ], but is much lower than the calculated value of the Ravi River, North-western India ( Table 5 ), which may be attributed to the geographical variation. Tactlessly, this research conveys the first effort to estimate the size at sexual maturity and optimum catchable length for this fish, hence comparisons with other findings will be required in the future.…”
Section: Discussionsupporting
confidence: 68%
“…Froese [ 42 ] suggested, the form factor assists to check whether or not the body form of individual fish in a particular population or else explicit species is considerably divergent from others. In this current study, the a 3.0 value was 0.0172 while Islam and Azom [ 36 ] reported a 3.0 value of 0.008 for this species from the Atrai River, Dinajpur, Bangladesh. The assessed a 3.0 for the population of G. cenia was inside the cutoff points 0.0172–0.0193 narrated by Froese [ 42 ]; proposing short and deep body shape in the Jamuna River.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations